Optimization of indoor air quality towards the control of mould formation by taguchi method - M Amin, Sri Yulis; Che Wahab, Nur Halizzah; Husin, Muhammad Riduwan (FAZ Publishing, 2020)
The formation of mould in an indoor environment is closely related to the poor Indoor Air Quality (IAQ) which can lead to various adverse health effects such as Sick Building Syndrome (SBS) and Building Related Illness (BRI). Hence, this study was conducted to investigate the relationship between mould formation and IAQ parameters in FKAAS building. The optimization of physical IAQ parameters such as air temperature (A), relative humidity (B) and air movement (C) is conducted by Taguchi Method with L9 Orthogonal Array (OA) at 3 different levels. The response output being measured is the level of carbon dioxide (CO2) and the noise factor was time at morning and evening. The data obtained has been referred to Malaysia Standard (ICOP-2010) and ASHRAE Standard 55-2013 to verify the IAQ contamination level. From the investigation, it was found that the optimized parameters are within the acceptable range of standard and the most significant factor towards the IAQ was air movement, followed by relative humidity and air temperature. The best optimized parameters can be noted as (A:1; B:3; C:3) which is air movement at 0.195 m/s, 61% of relative humidity and air temperature of 25.77 oC. As a conclusion, Taguchi method has proven to be a powerful tool to generate robust physical parameter of IAQ, regardless of time change. In addition, the IAQ parameter definitely influence the formation of mould, and was proven by various signs of visible mould formation which indicates the unhealthy state for the occupant to stay.